Peran Metode Kauny Quantum Memory Dalam Pembelajaran Al-Qur’an Untuk Memudahkan Hafalan Al-Qur’an Di Sdit Adzkia 1 Sukabumi - Eneng Sumarni; Siti Qomariyah (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
Learning methods are one of the factors that affect the quality of student learning outcomes, in every subject including Qur'an memorization lessons, there are several methods used by educational institutions in an effort to improve the quality of student learning outcomes that have been determined, including Qur'an memorization learning but most methods used use the left brain (Short Term Memory), very rarely in memorizing the Qur'an using the right brain is (Long Term Memory) then researchers analyze the Kauny Quantum Memory method is a method of memorizing the Qur'an with fun and comfort, can memorize quickly, Easy and live the meaning of each verse memorized. This study aims to find out how the Kauny Quantum Memory Method Implementation in learning to memorize the Qur'an to facilitate memorization at SDIT Adzkia 1 Sukabumi. This study used a qualitative descriptive approach of analysis with inductive data collection. The result of this research is that the Kauny Quantum Memory method is very suitable to be applied in learning memorization of the Qur'an at SDIT Adzkia 1 Sukabumi as an effort to make it easier for students to memorize according to the target that has been set, with the Kauny Quantum Menory method it is very fun for students, but all learning methods have disadvantages and advantages, with this method students are able to achieve their memorization targets according to the target easily and quickly.